PROFIL KINERJA GURU SMP NEGERI KABUPATEN MAGETAN BERDASARKAN PENILAIAN KINERJA GURU - Ernawati Setyaningrum; Karwanto Karwanto; Kaniati Amalia (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to map and describe the performance profile of public junior high school teachers in Magetan Regency based on the Teacher Performance Assessment (PKG) as a professional evaluation instrument. This study is important to obtain an empirical picture of the level of teacher performance as an indicator of the quality of learning and professionalism of educators at the junior high school level. Method: The study used a descriptive quantitative approach. A sample of 88 teachers was determined through proportional random sampling technique. Data collection was carried out through a five-point Likert scale questionnaire covering five performance indicators, namely learning planning, learning implementation, classroom management, learning evaluation, and professional responsibility. Results: The results showed that the majority of teachers were in the sufficient category (57.95%), followed by the good category (31.82%), less (7.96%), and very good (2.27%), and no teachers were found in the very poor category. These findings indicate that teacher performance has generally met the basic standards of professionalism, but is not yet fully optimal. Novelty: quantitative and structured mapping of teacher performance based on PKG at the district level as a basis for professional development and data-based decision-making.